A Bacterial Artificial Chromosome Library for Sequencing the Complete Human Genome - Osoegawa, Kazutoyo; Mammoser, Aaron G.; Wu, Chenyan; Frengen, Eirik; Zeng, Changjiang; Catanese, Joseph J.; de Jong, Pieter J. (Genome Research, 2001)
A 30-fold redundant human bacterial artificial chromosome (BAC) library with a large average insert size (178 kb) has been constructed to provide the intermediate substrate for the international genome sequencing effort. The DNA was obtained from a single anonymous volunteer, whose identity was protected through a double-blind donor selection protocol. DNA fragments were generated by partial digestion with EcoRI (library segments 1–4: 24-fold) and MboI (segment 5: sixfold) and cloned into the pBACe3.6 and pTARBAC1 vectors, respectively. The quality of the library was assessed by extensive analysis of 169 clones for rearrangements and artifacts. Eighteen BACs (11%) revealed minor insert rearrangements, and none was chimeric. This BAC library, designated as “RPCI-11,” has been used widely as the central resource for insert-end sequencing, clone fingerprinting, high-throughput sequence analysis and as a source of mapped clones for diagnostic and functional studies.The sequence data described in this paper have been submitted to the GenBank data library under accession nos. AQ936150–AQ936491.]